Validation of the Clinical Assessment Scale in Autoimmune Encephalitis in Chinese Patients - Zhang, Yingchi; Tu, Ewen; Yao, Chenxiao; Liu, Jia; Lei, Qiang; Lu, Wei (Frontiers in Immunology, 2021)
Background and Objectives The Clinical Assessment Scale in Autoimmune Encephalitis (CASE) is a scale for assessing severity in autoimmune encephalitis. We aimed to validate the CASE score in a Chinese population and evaluate its clinical significance. Methods Patients diagnosed with autoimmune encephalitis were recruited between June 2014 and May 2019 from two hospitals. CASE and modified Rankin Scale (mRS) scores were obtained. Data regarding clinical features, treatment, and available information were gathered from the hospital information system. Results Of the 176 patients with autoimmune encephalitis, 11 died and 14 had tumours. Ten patients received second-line treatment. The CASE scores of patients receiving second-line treatment were significantly higher (median CASE: 15) than in those receiving first-line treatment (median CASE: 8) (p<0.001). Twenty-two patients had poor functional status (mRS>2). Areas under the curve of CASE on whether functional status was poor at 1 year were 0.89 (p<0.001). Sixty patients were admitted to the intensive care unit (ICU), and the CASE scores were positively correlated with days in the ICU (r=0.58, p<0.001). There was no statistically significant association between the CASE scores and relapse (p=0.39>0.05). Additionally, the CASE scores were positively associated with the mRS scores (r=0.85 p<0.001). Conclusions The CASE score is suitable for the comprehensive assessment of Chinese patients with autoimmune encephalitis, which may help clinicians to select the appropriate intervention and estimate the disease severity and prognosis.